2007
DOI: 10.1002/ptr.2188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ergogenic potential of noni juice

Abstract: Morinda citrifolia (noni) fruit juice is an increasingly popular health food with many reported benefits, such as antioxidant and immunomodulatory properties. Traditionally, noni fruit was used by Polynesians to combat fatigue. Also, clinical studies have revealed that noni juice consumption improves quality of life scores related to physical functioning and energy levels. To further evaluate the ergogenic (antifatigue and endurance promoting) potential of noni juice, aged mice were pretreated orally with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Two clinical studies on athletes and post-menopausal women demonstrated the noni juice effect on improving endurance (Langford, Doughty, Wang, Clayton, & Babich, 2004;Palu, Seifulla, & West, 2008). Another in vivo study on aged mice, given increasing doses of Tahitian Noni Juice orally (10, 20 and 40 mL/kg body weight) showed significantly longer average time in both the swim test and the rotarod test when compared with young and aged control (Ma et al, 2007). However, the fruit have been associated with liver toxicity (Millonig, Stadlmann, & Vogel, 2005), while the leaves are consumed as vegetables after blanching since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…Two clinical studies on athletes and post-menopausal women demonstrated the noni juice effect on improving endurance (Langford, Doughty, Wang, Clayton, & Babich, 2004;Palu, Seifulla, & West, 2008). Another in vivo study on aged mice, given increasing doses of Tahitian Noni Juice orally (10, 20 and 40 mL/kg body weight) showed significantly longer average time in both the swim test and the rotarod test when compared with young and aged control (Ma et al, 2007). However, the fruit have been associated with liver toxicity (Millonig, Stadlmann, & Vogel, 2005), while the leaves are consumed as vegetables after blanching since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies on postmenopausal women and athletes validated the MC fruit juice increased stamina (Langford, Doughty, Wang, Clayton, & Babich, 2004;Palu, Seifulla, & West, 2008). Tahitian Noni Juice increased the swimming time and rotarod duration of old mice, when compared with young and aged control mice (Ma et al, 2007). However, the MC fruit were reportedly hepatoxic to certain individuals (West, Su, & Jensen, 2009) leaf are recommended (Serafini et al, 2011;West, Tani, Palu, Tolson, & Jensen, 2007).…”
mentioning
confidence: 99%
“…Moreover, the lack of effect on metastatic incidence in the MMTV- neu mice suggests that TNJ would not increase risk if the primary tumor cells are spreading outside the breast, which would be important for breast cancer patients taking TNJ for other health benefits or continuing problems that preceded cancer. Noni is reported in preclinical and clinical studies to increase energy and quality of life and decrease pain [4, 65, 66]; thus, its use may have potential benefits for cancer patients besides or in addition to its antitumor properties.…”
Section: Discussionmentioning
confidence: 99%